DEHYDROXYLATION OF FE3+, MG-RICH DIOCTAHEDRAL MICAS: (II) CATION MIGRATION - Muller F.; Drits V.A.; Tsipursky S.I.; Plancon A. (My University, 2000)
The quantitative interpretation of the reflection intensities of the SAED patterns of glauconites reveals the mechanism of migration of the octahedral sheet cations during heating up to 750°C. It confirms that Mg2+ has a greater ability than Fe3+ to migrate from cis- to trans-sites, as previously found by means of XRD pattern modelling. For samples heated to 650°C, the two formerly vacant trans-sites in the base-centred unit-cell become occupied, but differently, which leads to a primitive unit-cell, and the cis- sites remain filled almost entirely by Fe3+ only. The cation migration occurs through the nearest shared edges in the (010) and (310) directions. The samples heated to 750°C reveal a base-centred super-cell with A = 3 a and B = b. All Mg cations leave the cis sites to occupy completely four of the six available trans-sites of the super-cell. Migration also occurs through the shared edges in the (010) and (310) directions. The primitive unit-cell is not an intermediate step in the migration process leading to the super-cell. The existence of additional satellites in the SAED patterns of some crystals heated to 750°C corresponds to the existence of antiphase domains with a 3b/2 width and an antiphase shift of a/2.